The Potent In Vitro Skin Permeation of Archaeosome Made from Lipids Extracted of Sulfolobus acidocaldarius. (26th December 2013) - Moghimipour, Eskandar; Kargar, Mohammad; Ramezani, Zahra; Handali, Somayeh
Abstract : Archaeosomes are a new generation of liposomes that exhibit higher stabilities under different conditions, such as high temperatures, alkaline or acidic pH, and presence of bile salts in comparison with liposomes, and can be used in biotechnology including drug, gene, and vaccine delivery. The objective of this study was to prepare archaeosomes using lipid extracted from Sulfolobus acidocaldarius and evaluate their physicochemical properties. The lipids were extracted from S. acidocaldarius and assayed by High Performance Thin-Layer Chromatography (HPTLC). Archaeosomes were prepared using film method and methylene blue was used as drug model. They were characterized for their vesicle size and Differential Scanning Calorimetry (DSC) was used to investigate changes in their thermal behavior. The released amount of methylene blue was determined using a dialysis membrane and rat skin. HPTLC analysis of the extracted lipids showed that glycerol ether may be the major lipid with more than 78 percent probability. Results of particle size determination showed a mean size of 158.33 nm and the results of DSC indicated the possible interaction of methylene blue with lipids during the preparation of archaeosome. The addition of cholesterol significantly improved the encapsulation of methylene blue in the archaeosome so that the encapsulation efficiency was 61.66 ± 2.88%. The result of in vitro skin permeation showed that methylene blue could pass through skin model according to Peppas model and there was about 41.66% release after 6 h, whereas no release was observed through dialysis membrane. According to the results of the study, it is concluded that archaeosome may be successfully used as drug delivery system.